Oscillatoria sp. as a Potent Anti-phytopathogenic Agent and Plant Immune Stimulator Against Root-Knot Nematode of Soybean cv. Giza 111 - Ghareeb, Rehab Y.; Abdelsalam, Nader R.; El Maghraby, Dahlia M.; Ghozlan, Mahmoud H.; EL-Argawy, Eman; Abou-Shanab, Reda A. I. (Frontiers in Plant Science, 2022)
Root-knot nematodes (RKNs), Meloidogyne spp., are tiny soilborne parasites that can pierce the roots of a wide variety of plants. RKNs cause significant damage to the broad range of economically host crops like soybean and result in dramatic yield losses worldwide. To completely control RKNs, conventional plant protection strategies have been used, which, however, do not provide acceptable solutions. Therefore, it is crucial to develop an alternative control strategy that is environmentally friendly and economically sustainable. Cyanobacteria produced several bioactive toxins compounds, inhibiting hatching and causing immobility and mortality of RKNs. Therefore, we isolated, characterized, and identified a novel cyanobacterial strain. This strain was identified as an Oscillatoria sp. based on its microscopic examination and the 16S rRNA gene sequence. The aqueous and methanolic extracts of Oscillatoria sp. had antinematode activity against M. incognita. The percentage of mortality and egg hatching of M. incognita was significantly increased with the increase of time exposure to the Oscillatoria extracts. The aqueous extracts have significantly increased the percentage of RKN mortality and the reduction rate of egg hatching, compared with Oxamyl and methanol extract. In addition, water extracts significantly decreased the number of galls in Soybean root, egg masses, and female/root and decrease the % of J2S/250 g soil. Root and shoot lengths and dry weight and the chlorophyll content of soybean treated with Oscillatoria water extract were significantly higher compared with control. Gene expression of the plant defense system was monitored using four important pathogenesis-related genes, PR-1, PR-2, PR-5, and PR15, encoding enzymes contributing to plant defense. Based on the obtained data relating to defense gene expression, it was observed that the cyanobacterial algal extract induced the plant defense system